Professional Identity of Public Sector Monitoring and Evaluation Practitioners - Desta, Meseret Daniel (University of the Witwatersrand, Johannesburg, 2024)
The study sought to explore and map the qualitatively different ways M&E practitioners conceptualise their professional identity in the context of the public sector. The inquiry and its findings were contextualised by taking into account experiences of M&E professionals related to the institutional, managerial and administrative settings of their respective organisations as well as their views on the current status and professionalisation journey of M&E in South Africa. This helped to identify different factors that influence the construction and deconstruction as well as the reconstruction of Professional Identity of M&E practitioners in the sector. In addition, the investigation also looked into how Monitoring and Evaluation practitioners navigate the political and institutional context of the Public Sector and engage in the process of (re) examining their professional identities. The investigation employed a phenomenographic approach to identify, categorise and logically construct an outcome space that presents the qualitatively different ways M & E practitioners perceive their Professional Identity. Nine purposely selected M&E practitioners from the public sector participated in this qualitative study. Data was collected through interviews using a questionnaire composed of both semi-structured and open-ended questions. The phenomenographic analysis revealed four categories of descriptions that depict how M&E practitioners perceive their Professional Identity in a continuum. These categories, hierarchically arranged from least to most sophisticated are Curators of Development Data, Auxiliary to Programme Management, Patron of Accountability and Democracy, and Champions of Development and Transformation
A research report submitted n Partial Fulfillment of the Requirement for the Degree of Master of Management (MM) in the field of Governance (Public and Development Sector Monitoring and Evaluation) to the Faculty of Commerce, Law, and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: Professional Identity; Public Sector; Monitoring and Evaluation; SDG-8: Decent work and economic growth